Indigenous women's health in Amazonas: Challenges, practices, and perspectives on the use of contraceptive methods (Research, Society and Development, 2025)
Indigenous women's health represents a key area of focus for promoting health equity, especially regarding family planning. This study is limited to the analysis of the challenges in the use of contraceptive methods among women from the Kainã village, located in the municipality of Manaquiri (AM). The objective was to understand the cultural and structural barriers that influence access to and adherence to contraceptive methods. The methodology involved conducting an educational workshop with approximately 19 Indigenous women, including adolescents and women at different reproductive stages. Low adherence to contraceptive methods was observed, strongly influenced by cultural factors and limited access to healthcare services. It is concluded that it is essential to strengthen health education initiatives that respect traditional knowledge and promote intercultural dialogue.